A escala labirinto no diagnóstico diferencial entre transtorno do espectro autista e transtorno de linguagem na faixa etária de 2 a 4 anos - Benfica, Tainá Rossato (2023)
This study aimed to analyze the contribution of the Labyrinth Scale in carrying out the differential diagnosis of children with Autistic Spectrum Disorder (ASD) and Language Disorder (LD) aged between 2 and 4 years. The Labyrinth Scale was applied to 38 children with a clinical speech-language diagnosis of LD, 48 children with a medical diagnosis of ASD, and 28 with typical development (TD). The evaluations of the TD group and ASD group came from the database of the research Labyrinth group. The composition of the LD group had as an inclusion criterion children aged between two and four years, with delay in communication and receptive and/or expressive language domains, diagnosed by speech therapists and confirmed by the Dimensional Inventory for Child Developmental Assessment (DICDA). These children were in the therapeutic process with a diagnosis of LD in private clinics or on the waiting list of teaching clinics, complaining of language delay, in the cities of Santa Maria, Porto Alegre, Farroupilha, Rio Grande and Bagé (RS). After signing the free and informed consent form, those responsible filled out the DICDA questionnaire and the anamnesis of the Labyrinth Scale online or printed, and were consulted to complement the interview when necessary. The procedures that make up the Maze Scale assessment were applied with the children, in the presence of those responsible, in an individual room. Video analysis and data tabulation were carried out by the researcher and supervisor of this study. Statistical analysis was performed using the JASP software, version 0.15. The one-way ANOVA test was used to compare scores between groups. The Post Hoc Scheffe test was also used. The Labyrinth Scale score made it possible to differentiate the LD and ASD groups in the Social Interaction, Verbal and Non-Verbal Communication, and Rigid Behavior and Repetitive Gesture subscales. The biggest significant difference between the TEA and LD groups is in the Non-Verbal Communication subscale. The Scale showed a significant difference between the DT and LD groups in the subscales of Verbal and Non-Verbal Communication, and Rigid Behavior and Repetitive Gesture. These results show that the Labyrinth Scale offers the differential diagnosis of ASD, LD and TD, presenting itself as an effective instrument to help professionals to carry out a differential diagnosis in the childhood clinic.